Modelling the Genealogy and Character of Global Pentecostalism: An African Perspective (Part 1) - Hofmeyr, JW; Kalu, OU (Nederduitse Gereformeerde Teologiese Tydskrif, 2006)
This article uses Africa to illustrate that Pentecostalism in Africa did not originate from Azusa Street but churches that emerged from the Azusa phenomenon have participated in mission in Africa and influenced the character of contemporary expressions of the diffused movement. But local actors are constantly reshaping the movement. With reference to Pentecostalism in Africa, this article intends to argue that Pentecostal historiography differs from missionary historiography with regard to issues like geography, time, indigenous roots, the different forms of the movement and its theology.